Cultural Hybridity in The Kite Runner - Subedi, Narendra Raj (Journal of Development Review, 2023)
The Kite Runner is a novel written by Khaled Hosseini. The novel is a mirror to see the Afghan history, culture, religions, politics and many other aspects of the nation. Specifically, the novel evolves round the Afghan immigrants in Fremont, California. This paper attempts to reveal the issues of cultural differences between the two cultures: Afghan/Muslim and the American/Christian where the Afghan immigrants face cultural difficulties in a new land. In the colonial, post-colonial and post-modern societies people from across the world travel, migrate, immigrate and even settle in a new cultural location where they have to assimilate, resist or interpret the new culture. In the midst of it, this article will examine the readjustment of the immigrants in a culturally different location. Readjustment is not easy but can be made possible by their choice off cultural hybridization. In this context Homi K Bhabha, a post-colonial theorist is considered for the application part in the present study. For Bhabha the cultural space means neither the one nor the other but something else besides, in between. Neither this nor that so the third space is created for the cultural practice. The Afghan immigrants find the third space where they can rest their cultural pain. Certainly, the assumption of 'in between-space' will help to come out to the cultural problems of immigrants in the new land.